Time management practice and associated factors among health professionals working in public and private hospitals in Dessie City, Northeast Ethiopia: a comparative cross-sectional study - Yimer, Ali; Feleke, Amsalu; Yazachew, Lake; Ahmed, Mohammed; Seid, Seada; Adem, Mohammed; Mustofa, Semira Muhidin; Markos, Merkineh; Sirage, Nurye; Kassaw, Abdulaziz Kebede; Mustefa, Nuru Muhammed; Ali, Dawed; et al. (Frontiers in Psychology, 2024)
Background Time management is a widely ignored concern in all types of organizations, including the healthcare system, despite its crucial role in the achievement of personal and organizational goals. Therefore, determining the practice of time management and its associated factors among health professionals is of paramount importance. Objective We aimed to assess time management practice and associated factors among health professionals working in public and private hospitals in Dessie City, Northeast Ethiopia. Methods A comparative cross-sectional study was conducted from 24 March to 24 April 24 2021 among 660 health professionals (220 from private hospitals and 440 from public hospitals), who were randomly selected using a stratified sampling technique. A self-administered questionnaire was used to collect data. A multivariable binary logistic regression model was run separately for public and private hospitals. A p-value of < 0.05 and a 95% confidence interval were reported to be statistically significant. Results A total of 615 participants responded to the survey, which resulted in a response rate of 93.2%. The magnitude of good time management practice among health professionals in both public and private hospitals was reported to be 57.1% (95% CI: 53.5–60.8%). However, the magnitude differed between public [50.1% (95% CI:45.5–54.7%)] and private hospitals [70.9% (95% CI: 63.5–76.7%)]. Living with families (AOR: 5.39, 95% CI: 1.84–15.77), satisfaction with compensation and benefits (AOR: 7.83, 95% CI: 1.97–31.16), satisfaction with work autonomy (AOR: 7.10, 95% CI: 1.94–25.95), and having a good plan (AOR: 3.42, 95% CI: 1.15–10.13) were statistically significant predictors of time management practice in private hospitals. Satisfaction with an organizational policy and strategy (AOR: 2.34, 95% CI: 1.25–4.36), performance appraisal (AOR: 1.95, 95% CI: 1.13–3.36), work autonomy (AOR: 1.92, 95% CI: 1.12–3.27), and the good approach of employees toward time (AOR: 2.12, 95% CI: 1.26–3.58) were statistically significant predictors of time management practice in public hospitals. Conclusion The magnitude of a good time management practice in public and private hospitals in the study area was low. The practice was observed to be higher in private hospitals than in public hospitals. The study revealed that the magnitude and associated factors of time management practice vary between hospitals, indicating the need for targeted intervention.